Comparison of serum cytokines levels in normal-weight and overweight patients with first-episode drug-naïve major depressive disorder - Gao, Wenfan; Xu, Yayun; Liang, Jun; Sun, Yanhong; Zhang, Yuanyuan; Shan, Feng; Ge, Jinfang; Xia, Qingrong (Frontiers in Endocrinology, 2022)
Objective Abnormal levels of blood cytokines have been demonstrated to be associated with both excess weight and major depressive disorder (MDD). However, few studies have addressed the direct effect of body mass index (BMI) on basal serum cytokines in individuals with first-episode drug-naïve MDD. Methods A total of 49 patients with first-episode drug-naïve MDD were categorized into normal weight (18.5 ≤ BMI < 25 kg/m2) and overweight (25 ≤ BMI < 30 kg/m2) groups according to WHO-criteria. The severity of depressive symptoms was assessed using the 24-items Hamilton Depression Scale (HAMD-24). A total of 37 cytokines were measured using Multiplex Luminex Assays. The scores of HAMD-24 and the levels of serum cytokines between normal weight group and overweight group were compared. Multiple linear regression analysis was performed to evaluate the association between abnormal serum cytokines levels and group after adjusting for HAMD-24 scores. The correlation between BMI and the scores of HAMD-24 and the levels of serum cytokines was evaluated using Pearson correlation analysis. Results The scores of HAMD-24 in overweight group were significantly higher than normal weight group (t = -2.930, P = 0.005). Moreover, the levels of IL-1α, IL-1RA, IL-3, CXCL10, TNF-α, and ICAM-1 in overweight patients with MDD were significantly higher than those in normal-weight patients with MDD (all P < 0.05). Furthermore, after adjustment for HAMD-24 scores, there was a significant correlation between abnormal serum cytokines levels (IL-1α, IL-1RA, IL-3, CXCL10, TNF-α, and ICAM-1) and group (all P < 0.05). Additionally, BMI was positively correlated to the serum levels of IL-1α (r = 0.428, P = 0.002), IL-3 (r = 0.529, P < 0.001), IL-6 (r = 0.285, P = 0.050), IL-10 (r = 0.423, P = 0.003), IL-12 (r = 0.367, P = 0.010), IL-15 (r = 0.300, P = 0.036), CXCL10 (r = 0.316, P = 0.030), TNF-α (r = 0.338, P = 0.021), and ICAM-1 (r = 0.440, P = 0.002) in MDD patients. Conclusions These results provide direct evidence, probably for the first time, that overweight may be associated with several serum cytokines in patients with first-episode drug-naïve MDD. The underlying mechanisms are unclear and require further investigation.